Parliament and foreign policy in the eighteenth century - Black, Jeremy (Cambridge University Press, 2004)
This is a scholarly study of the British Parliament and its role in foreign policy during the eighteenth century, and the quality and impact of contemporary parliamentary debates. It also provides a major reassessment of the public debate over foreign policy.